Male partner involvement in postnatal care service utilization and its associated factors in Wolaita Sodo, southern Ethiopia, 2023 - Aklilu Adisu; Wubshet Estifanos; Genet Asefa; Fikre Moga Lencha; Addisalem Haile; Fekadu Abera Kebede (Frontiers in Global Women's Health)
BackgroundInvolvement of male partners in postnatal care (PNC) is an effective approach to improving maternal and child health outcomes. Despite this, it has been perceived as a woman's responsibility and continues to be a significant problem in developing countries, including Ethiopia. Furthermore, there is a paucity of evidence regarding male involvement during postnatal care in Ethiopia, particularly in the study area. Therefore, the purpose of this study was to assess the current status of male partners’ involvement in postnatal care and associated factors in the study area, Wolaita Sodo, in southern Ethiopia in 2023.MethodsA community-based cross-sectional study design was conducted on 629 participants from 1 April to 1 May 2023 using a multistage sampling technique. A pre-tested and structured questionnaire was used to collect data. Data were entered into EpiData version 4.6 and exported to Statistical Package for Social Science (SPSS) version 25 for analysis. Bivariable and multivariable logistic regression analyses were employed to identify factors associated with male partner involvement during postnatal care. The level of significant association in the multivariable analysis was determined based on a P-value of <0.05.ResultsThis study found that 32.95% [95% confidence interval (CI): 29.2–36.8] of male partners are involved in postnatal care service utilization. A higher maternal educational level [adjusted odds ratio (AOR): 2.95, 95% CI: 1.76–4.94], good knowledge of postnatal care services (AOR: 3.2, 95% CI: 1.93–5.3), good knowledge of danger signs and complications (AOR: 4.5, 95% CI: 2.39–8.48), a favorable attitude (AOR: 4.02, 95% CI: 2.50–6.45), distance (AOR: 1.91, 95% CI: 1.15–3.17), and cesarean delivery (AOR: 2.5, 95% CI: 1.39–4.60) were significantly associated with male partner involvement in postnatal care services.ConclusionIn this study, a male partner's involvement in their spouse's PNC service utilization was found to be low. Maternal educational status, good knowledge of PNC services, good knowledge of danger signs and complications, a favorable attitude, distance, and cesarean delivery were associated with male partner’s involvement in PNC. Therefore, strengthening awareness about postnatal care services and danger signs through health education and promoting a positive attitude toward postnatal services are essential.